Profit Taxation and Bank Risk Taking - Michael Kogler (Center for Economic Studies and Ifo Institute (CESifo), 2021)
How can tax policy improve financial stability? Recent studies suggest large stability gains from eliminating the debt bias in corporate taxation. It is well known that this reform reduces bank leverage. This paper analyzes a novel, complementary channel: risk taking. We model banks' portfolio choice under moral hazard and emphasize the `incentive function' of equity. We find that (i) an allowance for corporate equity (ACE) and a lower tax rate discourage risk taking and offer stability and welfare gains, (ii) a revenue-neutral ACE unambiguously improves financial stability, and (iii) capital regulation and deposit insurance influence the risk-taking effects of taxation.
Keywords: G21; G28; H25; 330; corporate taxation; tax reform; banking; risk taking; financial stability